Neurological complications in patients with SARS-CoV-2 infection: a systematic review - MUNHOZ, Renato Puppi; PEDROSO, José Luiz; NASCIMENTO, Fábio Augusto; ALMEIDA, Sergio Monteiro de; BARSOTTINI, Orlando Graziani Povoas; CARDOSO, Francisco Eduardo C; TEIVE, Hélio A Ghizoni (Arquivos de Neuro-Psiquiatria, 2020)
Background: As the COVID-19 pandemic unfolds worldwide, different forms of reports have described its neurologic manifestations. Objective: To review the literature on neurological complications of SARS-CoV-2 infection. Methods: Literature search performed following systematic reviews guidelines, using specific keywords based on the COVID-19 neurological complications described up to May 10th, 2020. Results: A total of 43 articles were selected, including data ranging from common, non-specific symptoms, such as hyposmia and myalgia, to more complex and life-threatening conditions, such as cerebrovascular diseases, encephalopathies, and Guillain-Barré syndrome. Conclusion: Recognition of neurological manifestations of SARS-CoV-2 should be emphasized despite the obvious challenges faced by clinicians caring for critical patients who are often sedated and presenting other concurrent systemic complications.
Keywords: Coronavirus Infections; COVID-19; Neurology; Guillain-Barré Syndrome; Encephalitis; Stroke